The effect of antibody on the degradation of a polysaccharide by the reticulo-endothelial system - Jenkin, C. R. (1967)
A galactan isolated from gum arabic was shown to be non-antigenic in mice. However, O-acetylated derivatives of this polysaccharide were antigenic and also gave rise to antibodies which reacted with the galactan. The degradation of the galactan and its O-acetylated derivatives in vivo by the liver and lungs of normal mice has been followed. It was found that, whereas, both the liver and lung degraded the galactan, O-acetylated derivatives containing 10–20 per cent by weight O-acetyl groups were degraded only by the lung. The breakdown of the acetylated polysaccharide by the lung was enhanced by added antibody under conditions where the antigen was in excess. These conditions also led to an enhanced antibody response. In contrast both degradation and antibody formation were inhibited when animals received antigen—antibody complexes in antibody excess. The significance of these results in relation to the anamnestic response is discussed.